Non-linear Inflation-Growth Nexus in Indonesia - Ahmad Albar Tanjung; Muliyani; Sirojuzilam Hasyim; Monika Andrasari; Syarifuddin (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose – This study primarily aims to assess the asymmetric effects of inflation on economic growth in Indonesia. Design/methodology/approach – The empirical work draws on annual time-series observations spanning 1990 to 2024. The data sources are the Central Statistics Agency, the World Bank, Bank Indonesia, the Ministry of Trade and Caldara & Iacoviell (2022) for the global geopolitics index. To capture the non-linear inflation and growth nexus in Indonesia, the Smooth Transition Threshold Regression (STR) framework is adopted. Global geopolitics, investment, government expenditure, and trade openness serve as the control variables. Finding/Results – For the retained specification, the Escribano-Jorda procedure points to a Logistic Smooth Transition Regression (LSTR) rather than an Exponential Smooth Transition Regression (ESTR). The estimates confirm that inflation, together with the controls, affects Indonesian growth asymmetrically. Within the lower regime, movements in inflation are positively and significantly linked to growth; global geopolitics, investment, and trade openness are positive yet statistically insignificant, whereas government expenditure exerts a significant positive influence on growth. In the non-linear component, the change in inflation turns significantly negative for growth. Over this segment, global geopolitics, investment, and trade openness are negative but insignificant, while government expenditure becomes significantly negative. A threshold for the change in inflation is identified at 3.42 per cent. Originality/Value – The contribution of the study lies in modelling the non-linear inflation and growth relationship through the STR method, an approach not previously deployed in the Indonesian setting, and in bringing a global geopolitical variable into the specification as a control.